Exploring the Academic English Literacy among Fourth Grade Students at Sunrise Elementary School, Kerobokan, Badung - Ni Made Rika Susanti Ningrum; I Gede Budasi; I Wayan Swandana (Journal of Educational Sciences, 2026)
This qualitative case study explored the implementation of academic English literacy among fourth-grade students at Sunrise Elementary School, focusing on classroom practices, teaching strategies, and encountered challenges. Data collection involved observations, interviews, and document analysis, which were analyzed using thematic analysis. The findings revealed that literacy was primarily practiced through reading and writing activities, supported by teacher strategies such as vocabulary pre-teaching, guided reading, modeling writing, questioning, and feedback. While these methods successfully supported students' basic literacy skills such as understanding vocabulary, identifying main ideas, and constructing simple sentences, students still faced significant challenges in higher-order academic literacy. Specifically, they struggled with critical thinking, analytical reading (e.g., making inferences), and coherent academic writing. In conclusion, although the current implementation effectively fosters foundational literacy, students require more intensive guidance and targeted practice to develop higher-level academic literacy skills. Consequently, teachers are encouraged to introduce more activities that promote critical thinking, analytical comprehension, and structured academic writing.